Severe mitral regurgitation is associated with increased copeptin levels in heart failure with reduced ejection fraction - (:unkn) unknown (VIA MEDICA, 2017)
Background and aim: The objective of this study was to assess the potential role of mitral regurgitation (MR) in the release of copeptin in HF patients with reduced ejection fraction (HFREF). Methods: The study included 63 patients of whom 33 had functional mild MR (Group 1) and 30 had functional severe MR (Group 2). The functional classes of the groups were both NYHA Class III. Blood samples for the determination of plasma copeptin and B-type natriuretic peptide (BNP) levels were obtained at the same day with the echocardiographic examination. Standard echocardiographic studies were performed. Results: Copeptin and BNP levels showed a substantial agreement in whole study group (Kappa level: 0.607, p < 0.0001). Also, copeptin and BNP showed a strong correlation and were both increased and significantly higher in Group 2 than Group 1 (p<0.001 and p<0.05, respectively). Left ventricular global longitudinal strain and LVEF values were similar in both groups. The study population were divided into two subgroups on the basis of copeptin median level (6.4 ng/mL), and the prevalence of severe MR were significantly higher in the above median copeptin subgroup. A linear regression analysis showed that the presence of severe MR was the only independent predictor of high circulating plasma copeptin level ( OR: 7.5 (95% CI 2.8-12.1), p = 0.002). Conclusions: Severe MR is an independent predictor of elevated plasma copeptin level in HFREF irrespective of systolic function.
Keywords: copeptin; heart failure; functional mitral regurgitation; TERMINAL PROVASOPRESSIN COPEPTIN; ARGININE-VASOPRESSIN; NATRIURETIC PEPTIDE; PROGNOSTIC MARKER; CARDIOVASCULAR-DISEASE; BIOMARKERS; PATHOPHYSIOLOGY; PREDICTION